Optimization of energy from photovoltaic cell using three port converter for home appliances - Kumar M, Jagadeesh; G, Jayanthi; ., Priyadharshni; S, Subhikshaa; K, Sivaranjani (International Journal of Engineering and Technology, 2018)
The main objective of this paper is to propose the significant usage of photovoltaic modules in household applications. This paper describes a compact but fully functional design by integrating basic converters to form a simplified single inductor converter structure while keeping minimum number of switches. The resultant converter is fully reconfigurable that all possible power flow combinations among the sources and load are achieved through different switching patterns. Single inductor converter module is used to simplify the structure while reducing the number of switches. This is fully configurable enabling all possible power flow combinations. The experimental behavior of this module from morning till evening is observed and the wave pattern of the subjective proposed results are recorded and verified.